Effect of Addition of Oleic Acid as a Template with Tetraethylorthosilicate (TEOS) as Source of Silica on Porosity Mesoporous Silica Material - Andriayani; Telambanua, Claresta Ingrid; Nainggolan, Hamonangan (Talenta Publisher, 2023)
Mesoporous silica material has been synthesized using tetraethylorthosilicate (TEOS) as a source of silica, oleic acid as a template, and 3-aminopropyltrimethoxysilane (APMS) as co-structure directing agents (CSDA). The synthesis of silica material was made with a variation in the mole ratio of TEOS: Oleic acid with a ratio of 1: 0.2; 1: 0.3; 1: 0.5; 1: 0.6; 1: 0.7; 1: 0.9, and 1: 1. A mixture between TEOS and APMS was added to a mixture of oleic acid, HCl 0.1N and demineralized water then stirred at room temperature for 2 hours. Then aging, the mix at 80oC for 48 hours until solids are formed. Product separation was used in the centrifugation method. The resulting solid was dried at 50oC, and to remove the template, calcined at 550oC for 6 hours. The product of XRD analysis has a wider diffraction peak that indicates an amorphous material. The FT-IR spectrum shows the Si-OH and Si-O-Si groups which area characteristic of silica material. The product of SEM analysis offers the presence of sheets and plates of particle forms with different sizes. Adsorption desorption isotherm (BET) shows an isotherm type IV curve, and dominant pore sizes are 1.945 and 4.588 nm.